(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
Determining the geometric or morphology and mechanical properties of joints and geomechanics of intact rock is a vitally important issue in predicting the behaviour of structures built inside or on rock masses. The joint morphology is significant because it affects the strength of the rock mass and controls the stability of the structures related to the rock masses. Until recently, joint morphology was introduced in a simple form which brought about models that are far from the inherent state of a rock joint. The work presented in this research introduces a new model to represent rock joint morphology which is very close to reality. For this research, Sarchawa marble mine joint systems are studied. According to this research, the morphology of each rock joint can be expressed as a mathematical equation. Using the output of this research, we can see a more realistic view of the rock masses. As a result, we can have better designs for structures correlated to rock masses, making the result better and more reliable.